Dexamethasone therapy for preventing delayed encephalopathy after carbon monoxide poisoning. (17th November 2015) - Li, Q; Song, JJ; Zhang, HY; Fu, K; Lan, HB; Deng, Y
Abstract : We investigated dexamethasone therapy for preventing delayed encephalopathy after carbon monoxide (CO) poisoning. Eighty healthy male rats were exposed to CO and randomly divided into four groups: hyperbaric oxygen treatment (H), treatment (D), combined hyperbaric and dexamethasone treatment (C), and a control (M) group in which the rats inhaled CO to coma in the hyperbaric oxygen chamber, then were removed without further treatment. Twelve rats were put into the hyperbaric oxygen chamber and treated with air for 60 min (N) group. An eight arm maze was used to evaluate cognitive and memory abilities of these mice. Serum myelin basic protein (MBP) levels were evaluated using ELISA, and magnetic resonance imaging was used to observe brain demyelination and morbidity associated with delayed encephalopathy. A sample of the hippocampus from each group was examined by light microscopy. Cognitive and memory functions decreased in the control group M. Three days after CO poisoning, the serum MBP level of each group increased significantly. On Day 10 after CO poisoning, the MBP levels in groups C and D decreased significantly, but returned to normal on Day 18. MBP levels in the M and H groups were elevated at all time points. Brain MRIs showed significant differences among C, D, H and control M groups. Hematoxylin & eosin staining of the hippocampus showed greater damage in the control M and H groups. Early dexamethasone treatment may be useful for preventing delayed encephalopathy after CO poisoning and may reduce serum MBP levels.